Search for a new scalar decaying into new spin-1 bosons in four-lepton final states with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physics letters, 2025)
A search is conducted for a new scalar boson S, with a mass distinct from that of the Higgs boson, decaying promptly into four leptons (ℓ=e, μ) via an intermediate state containing two on-shell, promptly decaying new spin-1 bosons Zd: S→ZdZd→4ℓ, where the Zd boson has a mass between 15 and 300 GeV, and the S boson has a mass between either 30 and 115 GeV or 130 and 800 GeV. The search uses proton-proton collision data collected with the ATLAS detector at the Large Hadron Collider with an integrated luminosity of 139 fb−1 at a centre-of-mass energy of s=13 TeV. No significant excess above the Standard Model background expectation is observed. Upper limits at 95% confidence level are set on the production cross-section times branching ratio, σ(gg→S)×B(S→ZdZd→4ℓ), as a function of the mass of both particles, mS and mZd.
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und weitere 2920
Gesehen am 19.01.2026